Note:- 1) If y = cotx ; then dy/dx = `-cosec^2(x)`

` `

2) If y = cosecx ; then dy/dx = -cosecx*cotx

Now,

`f(x) = y = cotx`

differentiating

`f'(x) = y' = -cosec^2(x)`

differentiating

`f''(x) = 2cosecx*cosecx*cotx`

or, `f''(x) = y'' = 2cotx*cosec^2x`

Note:- 1) If y = cotx ; then dy/dx = `-cosec^2(x)`

` `

2) If y = cosecx ; then dy/dx = -cosecx*cotx

Now,

`f(x) = y = cotx`

differentiating

`f'(x) = y' = -cosec^2(x)`

differentiating

`f''(x) = 2cosecx*cosecx*cotx`

or, `f''(x) = y'' = 2cotx*cosec^2x`